Using iVR to deliver optimal psychotherapy experience—current perspectives on VRET for acrophobia - Kvapil Varšová, Kristína; Juřík, Vojtěch (Frontiers in Psychology, 2024)
Immersive Virtual Reality (iVR) presents a promising avenue for treating acrophobia through Virtual Reality Exposure Therapy (VRET). This paper explores the current state of VRET for acrophobia, identifying significant technological and practical barriers that limit its effectiveness and hinder widespread adoption. Key challenges include the need for more advanced and realistic user experiences, and for the integration of biofeedback mechanisms. Additionally, the role of therapists remains crucial, as therapist-led VRET sessions demonstrate better outcomes compared to automated interventions. The potential of Collaborative Immersive Virtual Environments (CIVEs) to enhance VRET by simulating real-life interactions and improving patient-therapist engagement is also discussed. Future research should focus on developing comprehensive guidelines for CIVE design and evaluating integrated VRET and CIVE systems for treating phobias, including acrophobia. Addressing these issues will enhance the therapeutic experience, making VRET a more effective and accessible tool for treating acrophobia.